2015
DOI: 10.1111/hiv.12235
|View full text |Cite
|
Sign up to set email alerts
|

Transmission risk behaviour at enrolment in participants in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial

Abstract: Background A proportion of HIV-positive people have condomless sex. Antiretroviral treatment (ART) reduces infectiousness, but a substantial proportion of HIV-diagnosed people are not yet on ART. We describe baseline self-reported risk behaviours in ART-naïve START trial participants. Methods All START participants completed a risk behaviour questionnaire. Data were collected on sociodemographics, lifestyle factors, health and wellbeing status, and clinical status. Recent sexual behaviour and HIV transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…However, this association of knowledge of partner HIV serostatus may be evidence of use of seropositioning although we did not specifically present the question. Though seropositioning as a STI/HIV prevention strategy has been described in the global MSM and TGW community (Rodger et al, 2015; Snowden, Raymond, & McFarland, 2009; Xia et al, 2006), it has not been previously been reported in Peru (Clark et al, 2008). If alternative prevention methods like serosorting or seropositioning are being used, the behavioral effects of alcohol use prior to sex are likely to undermine the effectiveness of these strategies in that they depend on an accurate knowledge of a partner’s HIV serostatus.…”
Section: 0 Discussionmentioning
confidence: 95%
“…However, this association of knowledge of partner HIV serostatus may be evidence of use of seropositioning although we did not specifically present the question. Though seropositioning as a STI/HIV prevention strategy has been described in the global MSM and TGW community (Rodger et al, 2015; Snowden, Raymond, & McFarland, 2009; Xia et al, 2006), it has not been previously been reported in Peru (Clark et al, 2008). If alternative prevention methods like serosorting or seropositioning are being used, the behavioral effects of alcohol use prior to sex are likely to undermine the effectiveness of these strategies in that they depend on an accurate knowledge of a partner’s HIV serostatus.…”
Section: 0 Discussionmentioning
confidence: 95%
“…Accrual for the START trial was completed on 23 December 2013 with 4688 study participants enrolled from 215 sites in 35 countries. As part of the CAPRA programme of work, a substudy aimed to describe the baseline self-reported recent transmission risk behaviours and to assess sociodemographic, ethnic, lifestyle and other factors associated with these in START trial participants in order to examine the risk profile of these individuals (see Rodger et al 52 ).…”
Section: The Attitudes To and Understanding Of Risk Of Acquisition mentioning
confidence: 99%
“…• Chronic kidney disease, defined as eGFR < 60 mL/min/ 1.73 m 2 or dipstick proteinuria 1 + or greater, was present in 6.2% of participants [33]. • Approximately 17% of participants reported condomless sex with a serodiscordant partner in the 2 months prior to randomization [34]. • There was substantial geographical diversity in carrying out routine screening for transmitted ART-resistant virus, with screening much more likely to occur in resource-rich areas of the world [35].…”
Section: Overview Of the Baseline Monographmentioning
confidence: 99%
“…Below we highlight some characteristics of this unique cohort of individuals who were ART naïve and had CD4 cell counts > 500 cells/μL at study entry. The median age of the cohort was 36 years and 27% were women. The median CD4 cell count was 651 cells/μL and the median HIV RNA was 12 754 HIV‐1 RNA copies/mL . For 2.4% of participants the HIV RNA level was 50 copies/mL or lower . Approximately 19% of participants had two or more cardiovascular risk factors; 32% of participants reported smoking . Chronic kidney disease, defined as eGFR < 60 mL/min/1.73 m 2 or dipstick proteinuria 1 + or greater, was present in 6.2% of participants . Approximately 17% of participants reported condomless sex with a serodiscordant partner in the 2 months prior to randomization . There was substantial geographical diversity in carrying out routine screening for transmitted ART‐resistant virus, with screening much more likely to occur in resource‐rich areas of the world . Quality of life was mostly favourable; the average of the visual analogue scale of overall current health was 80.9 out of 100 . Changes in neurocognitive test performance will be compared for the immediate and deferred ART groups in 608 participants. At entry about 20% of participants had at least mild neurocognitive impairment . Changes in arterial elasticity will be compared for the immediate and deferred ART groups in 331 participants.…”
Section: Introductionmentioning
confidence: 99%